2016
DOI: 10.1164/rccm.201606-1183st
|View full text |Cite
|
Sign up to set email alerts
|

Executive Summary of the American Heart Association and American Thoracic Society Joint Guidelines for Pediatric Pulmonary Hypertension

Abstract: Although pulmonary hypertension (PH) contributes significantly to poor outcomes in diverse pediatric diseases, approaches toward the care of children with PH have been limited by the lack of consensus guidelines from experts in the field. In a joint effort from the American Heart Association and American Thoracic Society, a committee of experienced clinicians was formed to systematically identify, synthesize, and appraise relevant evidence and then to formulate evidence-based recommendations regarding the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
32

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 34 publications
1
46
0
32
Order By: Relevance
“…Caveolin (CAV-1) gene mutation has also been recently reported in association with activation of proliferative and anti-apoptotic pathways leading to vascular injury [38,39]. Genetic testing can be useful in children with IPAH or in families with HPAH to allow for definition of etiology and identification of family members at risk to be able to best counsel the family [40]. Testing should start with the proband and family members should be tested for the mutation expressed in the affected patient [15,41].…”
Section: Pathogenesis Of Pediatric Pahmentioning
confidence: 99%
“…Caveolin (CAV-1) gene mutation has also been recently reported in association with activation of proliferative and anti-apoptotic pathways leading to vascular injury [38,39]. Genetic testing can be useful in children with IPAH or in families with HPAH to allow for definition of etiology and identification of family members at risk to be able to best counsel the family [40]. Testing should start with the proband and family members should be tested for the mutation expressed in the affected patient [15,41].…”
Section: Pathogenesis Of Pediatric Pahmentioning
confidence: 99%
“…10 Some randomized controlled studies in preterm infants have found a benefit of iNO treatment in reducing the risk of chronic lung disease and/or death, 11e13 whereas others have not. 14e17 Nevertheless, consensus statements from the National Institutes of Health, 18 as well as the American Heart Association and American Thoracic Society, 19 concluded that the use of iNO in some preterm neonates, particularly those with PH or lung hypoplasia, may be beneficial. 18 An ongoing registry of preterm and late preterm or term neonates with HRF and PH in Japan is being conducted to assess the safety and efficacy profiles of iNO treatment in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Структурные изменения легочной сосудистой стенки закономерно сопровождаются функциональными нарушениями: прогрессирующим повышением легочного сосудистого сопротивления, нарушением перфузии. Увеличение постнагрузки и избыточное напряжение миокарда приводят к нарушению биоэнергетики кардиомиоцитов, запуская целый каскад нейрогормональных, биохимических и иммунологических реакций ремоделирования правого желудочка с последующим присоединением правожелудочковой, а в развернутой стадии тяжелой бивентрикулярной недостаточности [1][2][3][4][5][6][7][8].…”
unclassified
“…ЛГ у детей -состояние, сопровождаемое повышением среднего давления в легочной артерии ≥25 мм рт.ст., определяемое методом катетеризации сердца в покое у доношенных детей старше 3 мес. жизни [2][3][4][5][6][7][8].…”
unclassified
See 1 more Smart Citation